(untitled) (Ameghiniana, 2019)
The coral patch reef of La Manga Formation is the unique example of this kind of structure for the Upper Jurassic (Oxfordian) in Neuquén Basin. In previous works, four different genera of corals have been identified: Actinastrea, Australoseris, Garateastrea and Thamnasteria. A new taxonomic study on the specimens studied in previous works and new material leads to the rejection of the assignments to Garateastrea, Actinastrea and Thamnasteria, that where identified now as Australoseris, Stelidioseris and Etallonasteria respectively, while those identified originally as Australoseris, didn´t change their assignment. New results are based in a taphonomic analysis carried out to recognise the bias in the taxonomic analysis introduced by different preservational -taphonomic- grades. Three taphonomic grades were defined as Tg1-Tg3, with an increasing order of taphonomic distortion. The loss of microstructural features occurs for all these taphonomic grades, preventing the assignment at suprageneric to specific level. Additionally, those specimens with Tg2 and Tg3 suffered a change in their macrostructural features giving rise to apparent morphological details that lead to a wrong assignment. The Tg3 is the most frequently seen in the field. The material with this stage of preservation is not useful for taxonomic studies due to the loss of all diagnostic traits. Samples with Tg1 were the most useful for taxonomic studies because most of the macrostructural traits are preserved almost in their original shape. Taphonomic analysis of the specimens is necessary to carry out taxonomic studies for later measurements of richness and evenness.